The secondary attack rate (SAR) of SARS-CoV-2 in households: a systematic review - Bardhar, Shubhra; Khanna, Anoop (International Journal of Research in Medical Sciences, 2022)
Households are considered an essential setting for SARS-CoV-2 transmission due to the high intensity and frequency of interaction among family members. Many reports have suggested the high transmission risk of coronavirus disease-2019 in contacts within a household. Transmission parameter such as secondary attack rate is a helpful indicator used for assessing the risk of transmission in the household environment. The systematic review was done based on recommended guidelines of PRISMA for reporting. Three databases namely “Pubmed,” “Embase,” and “Web of science” were utilized for retrieving the articles. Each included study was evaluated based on the following criteria: study title, duration of the study, location, authors, design of the study, type and number of index cases, percentage of SAR, the number of contacts within the household, and other key findings. On the selection basis, 26 articles were included in the study reporting secondary attack rates in different countries. The majority of the studies reported household secondary attack rates to be higher among household adults and the old age group compared to children, SAR was also greater in spouses compared to other categories of household contact and females had slightly higher SAR compared to males. Often contact with index cases and symptomatic index cases increased the risk of SAR. Thus, this systematic study confirms that households have a significant role in the spread or transmission of SARS-CoV-2.